2018
DOI: 10.1371/journal.pone.0205426
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, causes, and consequences of preventable adverse drug reactions occurring in inpatients: A systematic review of systematic reviews

Abstract: BackgroundPreventable adverse drug reactions (PADRs) in inpatients are associated with harm, including increased length of stay and potential loss of life, and result in elevated costs of care. We conducted an overview of reviews (i.e., a systematic review of systematic reviews) to determine the incidence of PADRs experienced by inpatients. Secondary review objectives were related to assessment of the effects of patient age, setting, and clinical specialty on PADR incidence.MethodsThe protocol was registered i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 84 publications
3
43
0
1
Order By: Relevance
“…Among studies published in medicine to September 2019, in which the AMSTAR 2 was used as an instrument to evaluate the quality of SR/MA, 23 of 31 papers produced results similar to our study . In the six studies, the methodological quality of most (around 60%) of SRs was critical low to low . This suggests that in many areas, the methodological quality of SR is low or critical low.…”
Section: Discussionsupporting
confidence: 72%
“…Among studies published in medicine to September 2019, in which the AMSTAR 2 was used as an instrument to evaluate the quality of SR/MA, 23 of 31 papers produced results similar to our study . In the six studies, the methodological quality of most (around 60%) of SRs was critical low to low . This suggests that in many areas, the methodological quality of SR is low or critical low.…”
Section: Discussionsupporting
confidence: 72%
“…First developed in 2007 (as AMSTAR) to only evaluate the methodological quality of SRs that synthesize evidence from randomized trials, this appraisal tool has been further developed, as AMSTAR 2, in 2017 to expand its use to SRs of randomized trials and non-randomized studies 23. Since its release, AMSTAR 2 has been used widely in many umbrella reviews 27–33. AMSTAR 2 comprises 16 domains, 7 of them are critical domains as they strongly undermine the confidence in the conclusions of the SRs: 1 domain is related to protocol registration, 2 are related to search strategy (adequacy and justifying studies’ exclusion), 2 are related to the assessment of risk of bias of the included studies and its effect on SR conclusions, 1 is related to the method of evidence synthesis, and 1 is related to the publication bias (table 1).…”
Section: Methodsmentioning
confidence: 99%
“…A systematic review of systematic reviews of in-patients of all ages identified 13 reviews, which assessed 37 primary studies. Thirteen of the studies used prospective reporting (which tends to report higher rates than retrospective or voluntary reporting) and found an incidence of 3.13 (2.87, 3.38) per 100 patients, but due to the inadequate reporting of patients' ages, rates were not computed by age [4]. A prospective review of 6427 cases of adverse drug reactions recorded in the German Network of Regional Pharmacovigilance Centers in 2000-2008 identified that adverse drug reactions occurred in 3.3% of admissions to internal medicine wards, and that 60% occurred in those 70 and older.…”
Section: Background and Rationalementioning
confidence: 99%